Internal devaluation and the Portuguese Debt-to-GDP ratio - Azevedo, Maria Elisabete Vieira (2015)
With the entering into the euro, Portugal was able to benefit from very low interest rates, which led to a burst of borrowing either from public and private agents. Alongside this, there was the slowing down of the Portuguese PIB and deep increase in its public debtto- GDP ratio, leading the country to a snowball of problems that it is now trying to solve through an Internal Devaluation (henceforth ID). Portugal is now experiencing a public debt overhang problem. This study assesses whether Debt-to-GDP ratio is affected by a number of macroeconomic variables with special attention into unit labor costs (in representation for ID) in an annual sample from 1961-2012, through stationarity tests, followed by Johansen cointegration tests and a VEC Model approach in order to evaluate for both the short run and the long run relations. Granger causality is applied to the stationary macroeconomic variables. Four variables showed to have a long run relationship with the variable of interest, namely unit labor costs, domestic demand, exchange rate and exports. The VECM confirmed that the four variables do indeed present a long run relationship with Debt-to- GDP ratio. However, no short run relationship between the explanatory variables and the dependent variables appears to exist. Additionally, Granger causality tests indicate several causal relationships between the stationary variables. ID does have a long run impact on Debt-to-GDP ratio, but as it is shown, this does not happen in the short run, so convergence does take time as explained throughout this study.